Sedimentological and Petrophysical Properties of Sandstone Facies belonging to Lambir Formation at Tusan Beach, Miri, Sarawak. - Viet, Nguyen Hoang (Universiti Teknologi PETRONAS, 2014)
Understanding the sedimentological and petrophysical properties (porosity, permeability, density) of Early to Late Miocene Lambir Formation in Miri, Sarawak is essential for the reservoir characterization process of this formation’s equivalent located at offshore West Baram Delta. This project focuses on investigating a part of Lambir Formation, which is exposed in Tusan Beach area, along Miri - Bintulu coastline. The lithofacies of Lambir Formation in Tusan Beach area are originated from tidal influenced shallow marine environment, which could possibly make up good hydrocarbon reservoir. Sedimentary features related to shallow marine deposition such as ripple marks, cross beddings, and burrows are commonly seen in this formation. Two outcrops were observed and logged in order to investigate the facies characteristics and petrophysical properties of sandstones belong to Lambir Formation in the study area. In total five sandstone facies had been identified: i) Massive sandstone; ii) Trough cross-bedded sandstone; iii) Herringbone cross-bedded sandstone; iv) Tabular cross-bedded sandstone; v) Hummocky cross-bedded sandstone. Poro-perm results show high to very high permeability (1105mD to 3018mD) and very good porosity (25.3% to 28.7%) values in all samples, indicating excellent reservoir quality. Generally, samples belong to trough cross-bedded sandstone facies (sample 1, 5, and 6) recorded highest porosity and permeability values, followed by hummocky cross-bedded sandstones (sample 3 and 4) and lastly, herringbone cross-bedded sandstone (sample 2). Less mud content and coarser grain size in trough cross-bedded samples had contributed to this result. Observations also suggest that horizontal permeability is generally higher than vertical permeability of the same facies. High permeability anisotropy is observed in trough cross-bedded and hummocky cross-bedded sandstone facies, reflected through low kV/kH ratios, ranging from 0.42 to 0.55. Permeability distribution of onshore samples can be used as a proxy to predict the permeability trend of this formation offshore.